Labor Induction Outcomes With Outpatient Misoprostol for Cervical Ripening Among Low-Risk Patients [OP03-6C]. (May 2020) - Schneider, Allison N.; Tucker, Lue-Yen; Kandahari, Nazineen; Raine-Bennett, Tina; Mohta, Vanitha J.
Abstract : INTRODUCTION: Labor induction is becoming increasingly common. The objective of this study is to evaluate the effect of outpatient misoprostol for cervical ripening on inpatient time-to-delivery and maternal and neonatal outcomes. METHODS: We conducted an IRB approved retrospective cohort study of 10, 467 patients (559 outpatient, 9, 908 inpatient) who received misoprostol for cervical ripening at Kaiser Permanente Northern California hospitals between 2012 and 2017. Time-to-delivery and maternal and neonatal outcomes after misoprostol administration were analyzed with standard statistical tests. RESULTS: Patients induced with misoprostol in the outpatient and inpatient settings were comparable in demographics and predominantly nulliparous (70.3% and 64.3%, respectively). Patients who received outpatient misoprostol were more likely to have a cervical dilation of 3cm on admission (39.5% vs 9.7%, P < .0001). The outpatient misoprostol cohort had a shorter time between admission and delivery (20.6 [interquartile range (IQR) 12.4-31.7] vs 27.5 [IQR 19.2-37.4] hours, P < .0001), with no difference in mode of delivery or neonatal outcomes. Patients who received outpatient misoprostol were more likely to have a C-section for failure to progress in labor (14.0% vs 11.2%, P=.04), however the overall C-section rate was not significantly different between groups. Patients who received outpatient misoprostol had a higher rate of chorioamnionitis and a trend towards a lower maternal blood transfusion (14.3% vs 10.6%, P=.01; 0.7% vs 1.8%, P=.06, respectively). CONCLUSION: Outpatient misoprostol reduced inpatient time-to-delivery by a median of 7 hours with no significant differences in maternal or neonatal outcomes. An outpatient misoprostol protocol has the potential to decrease inpatient burden on Labor and Delivery.